Late traumatic LASIK flap perforation and displacement by bird bite - Shiuh-liang Hsu; Li-yi Chiu (Medicine, 2026)
Rationale: Traumatic flap dislocation is a rare but vision-threatening complication following laser in situ keratomileusis (LASIK), which may occur even many years after surgery. We report a unique case of late traumatic LASIK flap perforation and displacement caused by a bird bite. Patient concerns: A 40-year-old woman presented with blurred vision and ocular irritation in her left eye 1 week after being bitten by her pet bird. Diagnoses: Slit-lamp examination and anterior segment optical coherence tomography revealed traumatic LASIK flap displacement with irregular flap edges, epithelial ingrowth, and a paracentral full-thickness flap perforation. Interventions: Urgent flap repositioning was performed on the same day of presentation. Recurrent epithelial ingrowth surrounding the perforation site was subsequently managed with lubrication using autologous serum eye drops and sequential Nd laser treatments. Outcomes: Visual acuity improved from 20/50 at presentation to 20/25 after treatment. No recurrent epithelial ingrowth was observed during long-term follow-up. Lessons: LASIK flaps remain vulnerable to traumatic displacement even many years after surgery. Prompt flap repositioning and sequential management of epithelial ingrowth can achieve favorable visual outcomes in complex traumatic cases involving flap perforation.